THE IMPLEMENTATION OF KHUSNUL KHULUQ AS A STRATEGY FOR CHARACTER FORMATION OF GENERATION Z ADOLESCENTS IN THE ERA OF GLOBALIZATION - Dimas Azky Mauladani; Masrohatin Masrohatin; Mokhammad Miftakhul Huda (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
The moral degradation of Generation Z adolescents such as the crisis of empathy, cyberbullying, and social media addiction has become a serious issue in the era of globalization. Character education practices implemented so far tend to emphasize behavioral regulation through rules, reward–punishment mechanisms, and discipline programs, yet they have not addressed the root of the problem, namely the inner condition as the source of action. Previous studies have generally focused on observable behavioral changes, while classical moral literature still presents ethical concepts in an abstract manner and has not been sufficiently connected to the psychological context of modern adolescents. This study aims to formulate the implementation of khusnul khuluq according to Imam al-Ghazali as a strategy for character formation among Generation Z adolescents. The study employs a qualitative literature review method by analyzing Ihya’ Ulumuddin and contemporary sources on character education and Generation Z psychology. Data analysis follows the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. The findings indicate that khusnul khuluq is a stable inner disposition that spontaneously generates good actions and can be developed through mujahadah and riyadhah an-nafs. The novelty of this study lies in the development of an implementative model of khusnul khuluq for Generation Z through five stages: self-awareness, habituation of good deeds, utilization of digital technology, role modeling, and the formation of a supportive environment. In conclusion, character formation cannot be limited to external behavior alone but must begin with inner transformation to sustainably produce noble character.